I fugured it out never mind, i lost a not and needed to do some creative distribution
I have to prove the following statement using boolean identities for manipulation:
(a <--> (a --> b)) \/ ~b <==> (~b \/ a)
where: ~=not
-->=implication
<-->=biconditional
<==>=logical equivalence
V=Or
/\=And
I've been drilling away at it, and I got it to here:
(~a V b) V ~b
But I cant figure out how to take it any further, and judging where I am, it seems like I had to have done something wrong. Any suggestions?